2014
DOI: 10.1107/s2052520613034665
|View full text |Cite
|
Sign up to set email alerts
|

Towards the chemical control of molecular packing: syntheses and crystal structures of threetrans-[NiL4(NCS)2] complexes

Abstract: Three nickel(II) isothiocyanato complexes of the formula trans-[NiL4(NCS)2] (L = ethylisonicotinate, methylisonicotinate and 4-benzoylpyridine) have been prepared: [Ni(ethylisonicotinate)4(NCS)2] (I), [Ni(methylisonicotinate)4(NCS)2] (II) and [Ni(4-benzoylpyridine)4(NCS)2] (III). All three complexes are monomeric and have a distorted octahedral geometry around Ni(II). Despite their apparent molecular similarity, the crystal density of (III) (1.454 g cm(-3)) is significantly higher than that of (I) and (II) (bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…This approach is based on the thermal decomposition of discrete complexes of the general composition M­(NCS) 2 (L) 4 (M = divalent 3d metal cation; L = coligand) in which the metal cations are octahedral coordinated by two terminal N-bonded anionic ligands and four neutral coligands. Upon heating the coligands are usually removed in discrete steps, which enforces the formation of the coligand deficient compounds with the desired bridging coordination. , The synthesis and crystal structures of the discrete complexes with the composition M­(NCS) 2 ­(ethylisonicotinate) 4 (M = Co; 1-Co and M = Ni; 1-Ni ) are already reported in the literature. , Both compounds are also isotypic with very similar lattice parameters and consequently a very similar PXRD pattern (Table S5 and Figure S12). In the beginning, the homometallic compounds were synthesized (Figures S13–S16) to prepare physical mixtures that were investigated by PXRD (Figure S17).…”
Section: Results and Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…This approach is based on the thermal decomposition of discrete complexes of the general composition M­(NCS) 2 (L) 4 (M = divalent 3d metal cation; L = coligand) in which the metal cations are octahedral coordinated by two terminal N-bonded anionic ligands and four neutral coligands. Upon heating the coligands are usually removed in discrete steps, which enforces the formation of the coligand deficient compounds with the desired bridging coordination. , The synthesis and crystal structures of the discrete complexes with the composition M­(NCS) 2 ­(ethylisonicotinate) 4 (M = Co; 1-Co and M = Ni; 1-Ni ) are already reported in the literature. , Both compounds are also isotypic with very similar lattice parameters and consequently a very similar PXRD pattern (Table S5 and Figure S12). In the beginning, the homometallic compounds were synthesized (Figures S13–S16) to prepare physical mixtures that were investigated by PXRD (Figure S17).…”
Section: Results and Discussionmentioning
confidence: 79%
“…39,41−43 The synthesis and crystal structures of the discrete complexes with the composition M(NCS) 2 -(ethylisonicotinate) 4 (M = Co; 1-Co and M = Ni; 1-Ni) are already reported in the literature. 45,46 Both compounds are also isotypic with very similar lattice parameters and consequently a very similar PXRD pattern (Table S5 and Figure S12). In the beginning, the homometallic compounds were synthesized (Figures S13−S16) to prepare physical mixtures that were investigated by PXRD (Figure S17).…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…13 Besides, non-covalent interactions play an essential role in supramolecular chemistry, molecular biology and crystal engineering. [22][23][24][25] Various attempts have been made to elucidate and quantify them, including non-classical hydrogen bonding, 26,27 pÁ Á Áp stacking, 28,29 C-HÁ Á Áp 30 and CQOÁ Á Áp 31 interactions. All these interactions can be quantified by Hirshfeld surface analysis 29,32,33 based on tools such as d norm , shape index and curvedness surface properties and the fingerprint plots 32,34 display a quantitative picture of intermolecular contacts.…”
Section: Introductionmentioning
confidence: 99%
“…Recently the structures of three Werner complexes have been analysed in terms of their packing, and the results confirmed that nickel(II) thiocyanato complexes relate their crystal design to relatively weak forces such as hydrogen bonding or π⋯π interactions especially with pyridine derivatives or other similar ligands. 26 Compared with our previous work, 17 in which the rigidity of the isoquinoline ligand was found to play an important role in selectivity, the properties of this more flexible ligand, 4-vinylpyridine, are investigated. Here the crystal structures of the host, H, NiIJNCS) 2 (4-vinylpyridine) 4 with each of the seven polyaromatic hydrocarbon guests: indene (IND), naphthalene (NAP), azulene (AZU), fluorene (FLU), anthracene (ANT), phenanthrene (PHE) and pyrene (PYR) were obtained from solvent crystallisation.…”
Section: Introductionmentioning
confidence: 99%